A study on microbial fuel cell (MFC) with graphite electrode to power underwater monitoring devices - Ma'arof M.I.N., M.I.N; Chala, Girma T.*; Ravichanthiran, Saravanan (2018)
In recent decades, the world’s energy demand continues to increase while causing various types of environmental pollutions and global energy crisis. Microbial Fuel Cell (MFC) is a bio-electrochemical system that produces electricity by making use of chemical energy. Although Microbial fuel cells (MFCs) have the potential of generating electricity from a number of compounds, it is still far from achieving expected output due to irreversible reactions taking place in the anode and cathode compartments. Hence, the aim of this study was to generate power via MFC using graphite electrode. The MFC was fabricated by following a scientific procedure and several experiments were conducted to determine the voltages and power density produced with varied resistors. It was found that with the increase in oxygen supply, the voltage increases accordingly due to the increase in bacteria activity. However, as the catalyst decreases, the expected power output also decreases due to a decrease in bacteria activity. Conclusively, the following parameters are directly proportional to one another: voltage produced, bacteria activities and the existent/supply of catalyst.